2019
DOI: 10.1111/pai.13022
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional, population‐based study on the prevalence of food allergies among children in two different socio‐economic regions of Vietnam

Abstract: Background There is a paucity of data on the prevalence of food allergy (FA) in Vietnam. A cross‐sectional, population‐based study was conducted to evaluate the current prevalence of FA among 2‐ to 6‐year‐old children in two different regions in Vietnam. Method A structured, anonymous questionnaire, modified from published FA epidemiologic studies and based on EAACI guidelines, was distributed to parents/guardians of participating children in Hue City (urban area) and Tien Giang Province (rural area). Data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Independently of the type of school (public or private), a significant association of FA with asthma, atopic dermatitis, urticaria, allergic rhinitis, animals, and insect sting allergy was observed. These results support the notion that prevalence rates of self-reported FA and physician-diagnosed FA are more commonly reported in high-income than in low-income populations [ 21 ] and that there is a significant association of FA with other atopic diseases [ 25 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Independently of the type of school (public or private), a significant association of FA with asthma, atopic dermatitis, urticaria, allergic rhinitis, animals, and insect sting allergy was observed. These results support the notion that prevalence rates of self-reported FA and physician-diagnosed FA are more commonly reported in high-income than in low-income populations [ 21 ] and that there is a significant association of FA with other atopic diseases [ 25 ].…”
Section: Discussionsupporting
confidence: 85%
“…Our prevalence estimation of “immediate-type FA, current” is similar to the one reported in Mexican population (3.5% [ 12 ]), but it is lower than the prevalence rates estimated in other Latin American countries using the same instrument and evaluating populations with the same characteristics (El Salvador 5.3% and Chile 5.5%) [ 11 , 13 ]. Similar studies conducted in North America (USA 7.6% [ 5 ], Canada 7.14% [ 6 ]), Europe (6.86% in children aged 0 to 17 years old from all regions of Europe [ 18 ], 5.5% in children aged 6 to 12 years old from 10 European countries [ 8 ], 1.4 to 3.8% in school-aged children in eight European countries [ 10 ]), Asia (Taiwan 7.7% [ 19 ], Korea 4.06% [ 20 ], and Vietnam 8.9% [ 21 ]), and the Middle East (Lebanon 4.1% [ 22 ]; United Arab Emirates 8.0% [ 23 ]) have reported higher prevalence rates than the one reported in the present study. Various factors can influence the prevalence estimations such as the instruments used, the age range of the target population, and the criteria for defining allergy cases [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This immunologic adverse reaction not to toxic contaminants or pharmacologic characteristics of the food; it may be due to metabolic disorders of the host or idiosyncratic responses, such as lactase deficiency. [3][4][5] Due to the immature immune system in childhood and/or the inappropriate food introductory practices, children are more likely to develop food allergies than adults. 6 A current study revealed that about 20% of the adult population of developed countries and 40-50% of schoolgoing children are suffered by different allergic problems.…”
Section: Introductionmentioning
confidence: 99%
“…It has been increasing in the past twenty years and it represents a major public health problem in industrialized countries [8,9]. The highest rates are registered in economically and socially developed countries, such as the United States, Western Europe, Australia, and Asia [10,11]. Experts are concerned about environmental change, globalization and global industrialization, including the impact on the food industry, as not only the prevalence of food allergies is increasing, but the risk of severe reactions is also increasing [1].…”
Section: Introductionmentioning
confidence: 99%